SISTEM INFORMASI SIMPAN PINJAM PADA KOPERASI SATAHI MARSIURUPAN BERBASIS WEB - Sinaga, Septa Dewi; Nainggolan, Rena; Ginting, Mitha Christina (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
A savings and loan cooperative, the Satahi Marsiurupan Cooperative, located at Jalan Elang II No. 60 Perumnas Mandala Medan. The current savings and loan transaction system is still done manually. Cooperative management will be delayed due to manual data processing. The purpose of this research is to apply for a savings loan at the Satahi Marsiurupan Cooperative. The PHP programming language and MySQL database are used to create this web-based information system using structured programming techniques. This information system is provided to the Satahi Marsiurupan Cooperative to make it easier for members to receive information on savings and loan transactions from the management. As well as being able to provide solutions for speed, accuracy and accuracy in carrying out savings and loan data processing to obtain optimal results.